2006
DOI: 10.1108/02621710610645126
|View full text |Cite
|
Sign up to set email alerts
|

Chairman and chief executive officer (CEO): that sacred and secret relationship

Abstract: Abstract:The attention given to corporate governance has engendered little inquiry into one critical aspect of boardroom dynamics -the Chairman/CEO relationship. The reasons for the lack of attention to the Chairman/CEO dyad are highlighted, as well as the board and organisational performance reasons for maintaining role separation or entering into duality. Due to the poverty of understanding the effect of the Chairman/CEO relationship, a qualitative study was undertaken from which four themes emergedChairman'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 21 publications
8
89
0
1
Order By: Relevance
“…Even studies of 40 years ago (Hodgson et al, 1965) observed the "complementarity of functions" between chairman and CEO, with Stewart (1991) stating that the chairman role and executive director's role within the context of the UK's health services, are mutually inter-dependent. Kakabadse et al (2006), in their recent study of CEO/chair interrelations, reveal that the chair/CEO complementarity resembles a "generative dance" of constant attention to changes of mood and circumstance and, above all, the observable display of trust and respect for the other.…”
Section: Independent Directorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Even studies of 40 years ago (Hodgson et al, 1965) observed the "complementarity of functions" between chairman and CEO, with Stewart (1991) stating that the chairman role and executive director's role within the context of the UK's health services, are mutually inter-dependent. Kakabadse et al (2006), in their recent study of CEO/chair interrelations, reveal that the chair/CEO complementarity resembles a "generative dance" of constant attention to changes of mood and circumstance and, above all, the observable display of trust and respect for the other.…”
Section: Independent Directorsmentioning
confidence: 99%
“…In order to maintain the spirit of role separation, an emerging UK based trend is to recruit the chairman from existing non executive positions and not migrate the CEO to the position of chairman (Kakabadse et al, 2006). In fact, Higgs (2003, p. 81) specifically suggested that the "chief executive should not go on to become chairman of the same company" (Table II).…”
Section: Chairman: Role In Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…A working relationship between the CEO and Chair of the Board has been proposed as necessary for effective governance and pivotal to the performance of the Board (Roberts, 2002;Kakabadse et al, 2006), and to be at the heart of many other key organisational relationships (Roberts and Stiles, 1999). Trust, too, has been increasingly recognised as a central mechanism within organisational relations and governance, and the significance of trust has been highlighted in the literature of the CEO-Chair relationship (e.g.…”
Section: Introductionmentioning
confidence: 99%